Biochemical Composition of Zooplankton of Khour Al-Zubair Port, Southern Iraq - Ajeel, Shaker G.; Al-Anber, Luma J.; Al-Hamadany, Qusay H.; Hantoush, Abbas A.; . Al-Hassoon, Ahmed Sh. (Mesopotamian Journal of Marine Sciences, 2022)
The study of the biochemical composition of zooplankton, which constitutes an important part of the food chain, is an accurate criterion for the nutritional importance of these organisms, as they constitute the basic food for fish in their various stages of growth and other aquatic organisms of economic value. The present study aims to describe the significance of biochemical composition of marine zooplankton from Khour Al-Zubair. This study investigates the biochemical structure of zooplankton by studying their contents of proteins, lipids, ash, moisture and carbohydrates in the Iraqi marine waters (Khour Al-Zubair Port) during the period from August to December 2016. This has been accompanied by studying the water temperature and salinity. The results showed that the protein content of the zooplankton were 19.23 – 22.31 %, ash amounted to 3.86 – 4.45 %, while the lipids were 6.27 – 7.18 %, moisture were 65.82 –70.12 % and the carbohydrates 0.25 – 0.47 % wet weight